THE ROLE OF INNOVATIVE ACTIVITY IN THE DEVELOPMENT OF INDUSTRIAL ENTERPRISES IN UZBEKISTAN - Asimova Feruza Abdusattorovna (Scholar Express Journals, 2022)
In the article, the implementation of structural changes in the economy of our country and the attraction of investments for it, including the strategic goals and objectives of the reforms to attract foreign investments, especially direct investments, are innovative in the development of industrial enterprises. information about the location of the activity is given.
Keywords: location; investments; innovative; development